(3NOeGJ GdeYdheGJ (B/s - (3YdjGf, QHMj eUWais ((3YeGf(B: s (3OGQ UaGA(B, s, 2010)
(3eaGgje CSGSjI aj NOeGJ GdeYdheGJ , NOeGJ GdGYGQI deUGOQ GdeYdheGJ , GdNOeGJ GdeQLYjI , GdHHdjhZQGajG h GdNOeGJ GdHjHdjhZQGajI , NOeGJ GdJcTja h NOeGJ GdGSJNdGU , NOeGJ GdOhQjGJ , NOeGJ GdGMGWI GdLGQjI , NOeI GdHK GdGfJbGFj ddeYdheGJ , NOeGJ GdHMK aj bhGYO h fXe h THcGJ GdeYdheGJ , NOeI JOQjH GdeSJajOjf h NOeI KbGaI GdeYdheGJ , NOeGJ eYdheGJ CNQi , Jbjje NOeGJ GdeYdheGJ (B.s
(3eQGLY U(B.515s
Keywords: (3GdHK GdGfJbGFj ddeYdheGJs; (3GdeYdheGJs; (3NOeGJ GdeYdheGJs